Mining and resource mobilization for social development: The case of Nicaragua - Hilda María Gutiérrez Elizondo (United Nations Research Institute for Social Development (UNRISD), 2015)
This paper seeks to contribute to the global debate on the political and institutional contexts that enable impoverished countries to mobilize domestic resources for social development. More specifically, the paper aims to contribute knowledge and policy analysis about how to improve understanding of the politics of domestic revenue mobilization from the mining industry and resource bargains in developing countries. The potential impact of mining on resource mobilization for social development in Nicaragua will be analysed using two entry points: Firstly, economic benefits of mining and, secondly, political and institutional aspects. The main hypothesis of this study is that current political and institutional aspects weaken the states ability to mobilize resources for social development from the mining industry. These political and institutional aspects refer to the distribution of power and relationships between key actors; both in terms of who participate in negotiation processes and also in the outcomes of negotiations. At the local level, this is reflected in the way mining concessions and mining permits are granted. In the case of Nicaragua, resource bargains are being negotiated with mining companies. However, at present there are no citizen groups strong enough to pressure the state to raise the level of taxes paid by mining companies or improve environmental monitoring. This is evidenced by the fact that despite the boom in commodity prices in the mining industry, the fiscal regime has remained the same since its establishment in 2001. The results of the study indicate that the mining industry in Nicaragua provides some economic benefits. However, these benefits have been overshadowed by setbacks related to social and environmental impacts; specifically, the participation of civil society in decision-making.
Keywords: 330